2019
DOI: 10.1038/s41366-019-0485-y
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes and maternal obesity are associated with sex-specific changes in miRNA and target gene expression in the fetus

Abstract: Background/Objective-Pregnancies complicated by gestational diabetes (GDM) or maternal obesity have been linked to the development of diabetes, obesity and fatty liver disease later in life with sex-specific manifestations. Alterations in miRNA expression in offspring exposed to GDM and maternal obesity and effects on hepatic development are unknown. Here we describe how exposure to maternal obesity in utero leads to sex-specific changes in miRNA and target gene expression in human fetal liver. Methods-Candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…For example, small non-coding mRNAS, or miRNAs are epigenetic regulatory elements which perform fundamental roles in normal development, and can act as post transcriptional modifiers to control gene expression and translation [30]. Evidence suggests that sex differences exist in miRNA expression in the fetal brain of rodents [31], as well as in humans [32,33], and that maternal nutrition can alter miRNA expression in a sex-specific manner [34]. Furthermore, although in the context of osteoblast differentiation, previous studies have identified multiple miRNAs shown to be capable of regulating SATB2 [35,36], thus it is feasible that differential post-transcriptional regulatory activity contributes to SATB2 sex differences in the offspring VMN.…”
Section: Discussionmentioning
confidence: 99%
“…For example, small non-coding mRNAS, or miRNAs are epigenetic regulatory elements which perform fundamental roles in normal development, and can act as post transcriptional modifiers to control gene expression and translation [30]. Evidence suggests that sex differences exist in miRNA expression in the fetal brain of rodents [31], as well as in humans [32,33], and that maternal nutrition can alter miRNA expression in a sex-specific manner [34]. Furthermore, although in the context of osteoblast differentiation, previous studies have identified multiple miRNAs shown to be capable of regulating SATB2 [35,36], thus it is feasible that differential post-transcriptional regulatory activity contributes to SATB2 sex differences in the offspring VMN.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Brass et al [ 38 ] showed that placental uptake of oleic acid was suppressed and that the expression of the placental transporter CD36 was lower in male but not in female newborn of obese women. Recently, it was shown that miRNA expression in amniotic fluid and fetal hepatocytes is dependent on sex in offspring of women with GDM or obesity, although the mechanisms contributing to this phenomenon remain unknown [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Joshi et al, GDM confers an effect on offspring mediated by gender-specific alterations in miRNA and target-gene expression in the fetus [ 159 ]. miRNA was analyzed in the amniotic fluid (AF) of 20 women with and 20 without GDM in the second trimester [ 159 ]. The AF of women with GDM was found to be upregulated by miR-199a-3p , miR-1268a , and miR-503-5p .…”
Section: Epigenetic Modifications In Gdmmentioning
confidence: 99%